Mapping of Land Suitability for Growing Tobacco (Nicotiana tabacum L.) Under Various Slope Using Geographic Information Systems - Mujiyo Mujiyo; Daradinda Surya Irawaningsih; Slamet Minardi; Ongko Cahyono (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The study aims to identify the classes and the determinant factors of land suitability of Tobacco in order to provide recommendations for land management as an effort in increasing the development of Tobacco in Eromoko District, Wonogiri Regency, Indonesia. This research used a descriptive-exploratory approach by field surveys, laboratory analysis, and matching the data with growth requirement characteristics for Tobacco crops. The field survey was carried out based on a working map, namely the Land Mapping Unit (LMU), overlaid maps of soil type, slope, and rainfall. Research results illustrated that 18 LMUs were included in the marginally suitable class (S3) (4,968.78 ha, about 51% of research area) with limiting factors wa; oa; nr; na; eh, and 8 LMUs were included in the unsuitable class (N) (4,919.11 ha, about 49% of research area) with limiting factors N and eh. This study provide information about the land suitability class and the limiting factors each area to determine the potential success of Tobacco cultivation and make suitable improvement efforts. Keywords: Hilly land, Land management, Limiting factors, Sustainable agriculture, Tobacco growth potential.